Metabolomics Unraveling the Biochemical Insight of High Altitude Diseases and Sepsis A Narrative Review - Siddiqui, Mohd Adnan; Gupta, Upasna; Siddiqui, Mohammed Haris; Azim, Afzal; Sinha, Neeraj (Defence Life Science Journal, 2024)
High altitude diseases and sepsis may seem distinct at first glance, but there are underlying physiological similarities that lie in their responses to hypoxia, tissue dysfunction, inflammation, and multi-organ failure conditions. Understanding these commonalities can help medical professionals draw parallels between them and apply relevant knowledge to improve patient care and treatment.In this direction,a literature review of metabolomics-based studies has been done for high-altitude diseases and sepsis, and the panel of common disease-related metabolic markers and associated pathways areunraveled. Themetabolic pathways found dysregulated in both conditions are amino acid metabolism, lipid metabolism, energy metabolism, inflammatory response-related metabolism, bile acid metabolism, and purine and pyrimidine metabolism.